2014
DOI: 10.1063/1.4874334
|View full text |Cite
|
Sign up to set email alerts
|

The formation of reverse shocks in magnetized high energy density supersonic plasma flows

Abstract: A new experimental platform was developed, based on the use of supersonic plasma flow from the ablation stage of an inverse wire array z-pinch, for studies of shocks in magnetized high energy density physics plasmas in a well-defined and diagnosable 1-D interaction geometry. The mechanism of flow generation ensures that the plasma flow (Re M $ 50, M S $ 5, M A $ 8, V flow % 100 km/s) has a frozen-in magnetic field at a level sufficient to affect shocks formed by its interaction with obstacles. It is found that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
49
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 35 publications
(52 citation statements)
references
References 20 publications
3
49
0
Order By: Relevance
“…This setup is interesting as it allows the study of the interaction of magnetised flows with external obstacles. 7 These data demonstrate the dynamic range of sensitivity achieved by this interferometer; the peak density in this plot, ∼5 × 10 18 cm −2 corresponds to ∼20 fringe excursions, while the accuracy of the analysis method is conservatively estimated at ∼1/5 of a fringe shift (∼4 × 10 16 cm −3 ). This corresponds to a dynamic range of ∼100.…”
Section: Laser Interferometric Imagingmentioning
confidence: 97%
See 3 more Smart Citations
“…This setup is interesting as it allows the study of the interaction of magnetised flows with external obstacles. 7 These data demonstrate the dynamic range of sensitivity achieved by this interferometer; the peak density in this plot, ∼5 × 10 18 cm −2 corresponds to ∼20 fringe excursions, while the accuracy of the analysis method is conservatively estimated at ∼1/5 of a fringe shift (∼4 × 10 16 cm −3 ). This corresponds to a dynamic range of ∼100.…”
Section: Laser Interferometric Imagingmentioning
confidence: 97%
“…As an example, Figure 2 contains 1053 nm interferometry data captured during an experiment carried out to measure the B field embedded in an outflow of plasma produced by an inverse cylindrical wire array; 7,19,20 (b) shows a sideon schematic view of this load configuration, (c) shows the n e dl map that results from analysis of interferograms (d) and (e) using the methods described above. The inverse wire array produces ablation streams which are accelerated radially away from the array axis due to the reversal of the standard wire array z-pinch magnetic field topology.…”
Section: Laser Interferometric Imagingmentioning
confidence: 99%
See 2 more Smart Citations
“…The ablated plasma is accelerated away from the wires, reaching a velocity of ∼50 km=s within the first 1-2 mm, and thereafter propagates with an almost constant velocity. Previous measurements [19,20] have demonstrated that the plasma flows generated by a single exploding wire array have a frozen-in, azimuthal, advected magnetic field (B ∼ 2T), and are super-fast-magnetosonic. The arrays used in the current experiments consist of 16, 40 μm-diameter Al wires, 16 mm in length, positioned on a 16 mm diameter [ Fig.…”
mentioning
confidence: 99%